ANALYSIS OF DEVELOPMENT IN INDONESIA'S INCOME DISTRIBUTION IN THE VILLAGE LEVEL, CITY AS WELL AS VILLAGE AND CITY PERIOD 2011.3- 2018.3 - SUGIARTININGSIH,; BELA PUTRI, ANESA; RICKY IQBAL, MUHAMMAD; DAFI MAHESA, MAULANA; TAMIYANTI, WITARI (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the community economic system is to realize equitable distribution of income throughout Indonesia. The Indonesian government since the beginning of development has tried hard to improve it in order to achieve social welfare. The purpose of this study is to find out the development of inequality in Indonesia's income distribution at the village, city and village and city levels in the period 2011.3-2018.3. The phenomenon is that the income distribution gap in Indonesia is still high at the village, city and village and city levels. From the results of data processing shows that during the period under study the development of inequality in income distribution decreased in the three regions. The main factor is the large role of the government in providing infrastructure in the village with the formation of the Ministry of PPDT and Law No. 6 of 2014 concerning PID. Whereas in the City with the opening of business opportunities for foreign investors, increasing the competency of vocational students, the creativity of the informal sector and the rise of the entrepreneurial spirit and societalism. As for the Village and City the role of the government is to improve infrastructure that supports the digital industry and the tourism sector.